CURRENT STATE OF PROFESSIONAL TRAINING OF FUTURE MUSICAL ART TEACHERS FOR EDUCATIONAL INCLUSION - Natalia Ovcharenko (National Academy of Educational Sciences of Ukraine, 2019)
The article deals with the problem of professional training of future musical art teachers for teaching students with special educational needs. The purpose of the article is to present the findings of the research on the current state of professional training of future teachers of musical art for educational inclusion in Ukraine. The author underlines that the Law of Ukraine "On Education" (2017) states that inclusive education is a system of state-guaranteed educational services based on the principles of non-discrimination, respect for human diversity, effective involvement and inclusion in the educational process of all its participants. The Law guarantees the inclusion of persons with special educational needs into the general educational process. However, the findings of the research revealed that most future teachers of musical art are not at all or only partially trained to work with students with special educational needs. In order to improve the professional training of the future musical art teachers, the author proposed: to update the normative base of art education; to substantiate the organizational and methodological foundations of professional training of future musical art teachers for educational inclusion; to develop a system of appropriate training for educators of higher educational institutions; to create pedagogical conditions aimed at formation of motivations in students for artistic and educational inclusion; to level up the material and technological support of higher education institutions.